An analysis of the money market linkages between South Africa and selected major world economies - Barnor, Joel A (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
Globalisation and financial liberalisation has increased the linkages across countries in recent times. The existence of money market links has important implications for both domestic monetary policy and for investment decisions. This study examines the linkages between South Africa's money market and selected major international money markets. The objectives of the study are firstly to examine the links between the repo rate of South Africa and the central bank rates of the EU, Japan, UK and US. Secondly, is to compare the influence of domestic and foreign monetary policy decisions on South Africa's money market. The third objective is to examine the long run relationship between the South African money market and the money markets of its major trading partners. Three estimation techniques are used to examine the different links. Principal components analysis, four tests of cointegration, and stationarity tests of the spreads/risk premium between South Africa's interest rates and the interest rates of the other countries. All three techniques show that there is no long-run link between South Africa's central bank rates and the central bank rates of the other countries. This shows that the repo rate does not depend on movements in other central bank rates. Domestic money market interest rates respond strongly to changes in the repo rate whilst showing no dependence on central bank rates of the other countries. This confirms the autonomy of the South African Reserve Bank in carrying out policy objectives. When the risk premium is accounted for under the third technique, evidence of integration is found. This indicates that the risk premium plays a crucial part in the level of integration between South Africa and the countries included in the study.
Keywords: South African Reserve Bank; Banks and banking, Central -- South Africa; Money market -- South Africa; Monetary policy -- South Africa; Foreign exchange rates -- South Africa; International economic relations; Interest rates -- South Africa; Financial institutions -- South Africa